Parametric Sensitivity Study to Correlate Static and Dynamic Adsorption during Polymer Flooding - AL-HAJRI, SAMEER (2019)
Polymers are often added with water as viscosifier to improve oil recovery from hydrocarbon reservoirs. However, a part of the injected polymer is lost in porous media by adsorption on surfaces, mechanical entrapment in pores, and hydrodynamic retention in stagnant zones.